The Contribution of Historical and Morphological Studies on Herbarium Specimens to a Better Definition of Chara pelosiana Avetta (Charales, Charophyceae) - Anna Millozza (MDPI AG, 2021)
The lectotype of Chara pelosiana Avetta 1898 was designated in 2000 by Langangen, who merged the species with Chara fibrosa Agardh ex Bruzelius. Chara pelosiana belongs to the section Agardhia Wood, but the true identity of the species has yet to be confirmed. The purpose of this work is to show some historical and morphological findings regarding this enigmatic species, on the basis of the analysis of herbarium specimens. The original material, which was studied by Avetta, is missing in Italian herbaria, but portions of it have been found in the Herbarium of Jena. Historical research on botanists related with this species resulted in the discovery of several specimens to be considered “original material”, and new unpublished localities in Northern Italy. Morphological observations have been made on portions of herbarium specimens as a contribution to unveil the taxonomic identity of this taxon. The specimens are diplostichous with ecorticate branchlets, have stipulodes in a single row, one or two per branchlet, and spine cell up to 1 mm long.